2005
DOI: 10.1093/humrep/dei286
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of retinoic acid on embryo development and the selective expression of retinoic acid receptors in mouse blastocysts

Abstract: This is the first evidence to show the impacts of RA on mouse blastocysts in vitro and any carry-over effects in the uterus. There is a retardation of early postimplantation blastocyst development and then subsequent blastocyst death. Our findings also show that there is some degree of selective induction of retinoic acid receptors when excess RA is administered to the blastocysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
26
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 41 publications
8
26
2
Order By: Relevance
“…Too much or too little exposure to retinoids, at the wrong stage or at the wrong time, can adversely affect embryo development (Sporn and Roberts 1991;Huang et al 2006;Rodríguez et al 2007). In the present study, the highest concentrations of both metabolites (500 nm RA and 12 500 nm ROH) were cytotoxic because they prevented oocytes from achieving nuclear maturation.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Too much or too little exposure to retinoids, at the wrong stage or at the wrong time, can adversely affect embryo development (Sporn and Roberts 1991;Huang et al 2006;Rodríguez et al 2007). In the present study, the highest concentrations of both metabolites (500 nm RA and 12 500 nm ROH) were cytotoxic because they prevented oocytes from achieving nuclear maturation.…”
Section: Discussionmentioning
confidence: 47%
“…There could be species-specific differences in the susceptibility to retinoids, with varied requirements during IVM in order to protect oocytes from detrimental effects on the one hand and from the epigenetic influences of retinol on the other, as has been reported by several authors (e.g. Gomez et al 2003;Huang et al 2006). The different concentrations of retinoids used between studies could also have been responsible for these discrepancies, given that the effects of these compounds are dependent on their concentration Livingston et al 2004;Lima et al 2006).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, the fetal weight was lower in the ethanol-treated group than the controls (552 ± 81 mg versus 503 ± 69 mg; P < 0.05), whereas the fetal weight was similar to the controls for the group receiving both dietary resveratrol and ethanol (540 ± 77 mg). We also examined the proportion of fetuses weighing over 600 mg, which is an important indicator for embryo and fetus development (Huang et al, 2006). Compared to controls, the ethanol-pretreated group had 7% fewer fetuses weighing over 600 mg, whereas 35% of the fetuses weighed were treated with or without resveratrol (10 M) for 1 h, followed by 0.5% ethanol for another 4 h. Blastocysts were observed in culture for 72 h post-treatment.…”
Section: Effects Of Resveratrol On the Disruption Of Blastocyst Develmentioning
confidence: 99%
“…Overall, fetal weight was lower in the 25-50 mM EGCG-treated group, compared to the control group ( Figure 4C). Previous investigations, including a recent report by our group, showed that 35-40% of fetuses weigh more than 600 mg, with the average weight of total surviving fetuses being approximately 600 AE 12 mg in the untreated control group at day 18 of pregnancy in a mouse embryo transfer assay (Chan, 2006(Chan, , 2009, 2008Huang et al, 2006). Fetal weight is an important indicator of developmental status.…”
Section: Effects Of Egcg On Blastocyst Developmental Potential In Vivomentioning
confidence: 94%